White matter injury, cholesterol dysmetabolism, and APP/Abeta dysmetabolism interact to produce Alzheimer’s disease (AD) neuropathology: A hypothesis and review - Sharp, Frank R.; DeCarli, Charles S.; Jin, Lee-Way; Zhan, Xinhua (Frontiers in Aging Neuroscience, 2023)
The amyloid cascade is the leading hypothesis for the cause of Alzheimer’s Disease (AD). The failure of clinical trials based on this hypothesis has raised other possibilities. Even with a possible new success (Lecanemab), it is not clear whether this is a cause or a result of the disease. With the discovery in 1993 that the apolipoprotein E type 4 allele (APOE4) was the major risk factor for sporadic, late-onset AD (LOAD), there has been increasing interest in cholesterol in AD since APOE is a major cholesterol transporter. Recent studies show that cholesterol metabolism is intricately involved with Abeta(Aβ)/amyloid transport and metabolism, with cholesterol down-regulating the Aβ LRP1 transporter and upregulating Aβ RAGE receptor, both of which would increase brain Aβ. Moreover, manipulating cholesterol transport and metabolism in rodent AD models can ameliorate pathology and cognitive deficits, or worsen them depending upon the manipulation. Though white matter (WM) injury has been recognized in AD brain since Alzheimer’s initial observations, recent studies have shown abnormal white matter in every AD brain. Moreover, it has been shown there is age-related WM injury in normal individuals that occurs earlier and is worse with the APOE4 genotype. Moreover, WM injury precedes formation of plaques and tangles in human Familial Alzheimer’s Disease (FAD) and precedes plaque formation in rodent AD models. Restoring WM in rodent AD models improves cognition without affecting pathology. How the amyloid cascade, cholesterol and white matter injury relate to AD pathogenesis is unclear. Based upon the above in addition to a review of the literature, we postulate that myelin injury contributes to cholesterol release from myelin and cholesterol dysmetabolism which contributes to Abeta dysmetabolism, and with genetic and AD risk factors, leads to amyloid plaques. Increased Abeta damages WM myelin to form a vicious injury cycle. Thus, white matter injury, cholesterol dysmetabolism and Abeta dysmetabolism interact to produce AD pathology. We further postulate that the primary initiating event could be related to any of the three, with age a major factor for WM injury, APOE4 and other genes a factor for cholesterol dysmetabolism, and FAD and other genes for Abeta dysmetabolism.